VAGINAL BIRTH AFTER CAESAREAN SECTION - Abbasi, Aziz-un- Nisa (Journal of Ayub Medical College Abbottabad, 2012)
Nobody can deny the fact that caesarean section is a life saving obstetrical procedure for both mother and the baby. Decision for caesarean section should be made by experienced and qualified obstetricians. The well known principles of ethics like: autonomy, beneficence, nonmaleficence, and justice should be followed by the attending doctors. Based upon their knowledge, skills, and experience, decision of the obstetrician should be deemed ethical without suspecting their motives. Pre-requisites for VBAC: 1. Previous caesarean section performed for nonrepetitive causes like, breech presentation placenta previa, and foetal distress etc.1 2. Time interval between previous caesarean section and current pregnancy should be minimal 2 years. Week scars will rupture easily if time interval between previous caesarean section and present pregnancy is less than 2 years. In Pakistan 80% pregnancies are unplanned and many patients report in labour within 9 months of previous c-section. Measurement of uterine scar thickness by ultrasound scan is not so far a good predictor of scar integrity and is still in experimental stages.2 3. In current pregnancy patient should be booked with a qualified obstetrician from the beginning of the pregnancy. 4. Pregnancy is uncomplicated and low risk, if there is any added problem like abnormal foetal presentation, twin pregnancy, IUGR, macrosomic baby hypertension, uncontrolled diabetes, and bad obstetrical history when caesarean section is preferred over VBAC. 5. All patients with previous c-section should be assessed by a qualified Obstetrician in last month of pregnancy.3 6. It should preferably be spontaneous labour. Induction with oxytocin and prostaglandin should be avoided due to increased risk of scar rupture leading to high perinatal and maternal mortality.4,5 7. Patients should take labour in hospital that is well equipped having facilities of continuous foetal monitoring, cardiotocography (CTG), and continuous CTG monitoring -a mandatory requirement for the patient on trial of VBAC. Only signs of impending scar rupture are CTG abnormities (sudden onset of late deceleration).6 Labour wards of tertiary care hospitals in Pakistan are over worked where high risk and critical patients are referred. It is not possible to apply continues CTG on 50-60 labouring patients. Presently 2-3 CTG machines are available in some hospitals. Caesarean section on demand: Caesarean section on demand is on the rise for social reasons. Obstetricians cannot reject the demand of the patient for elective caesarean section. Patients should be thoroughly counselled about the pros and cons of vaginal delivery vs caesarean section.7 After thorough counselling final decision about the mode of delivery has to be the choice of the patient. With everything fine still there are 10-15% chances of caesarean section in patients who are in labour (Vagina delivery cannot be guaranteed!). Moreover, incidence of prenatal mortality is 2- 3 fold higher in emergency caesarean section compared to elective caesarean section, and maternal mortality is 1.5-2 folds higher in emergency caesarean section.8-10 Vaginal delivery is a retrospective diagnosis and nobody can guarantee, normal delivery before hand. In modern obstetrics there is no place for difficult vaginal delivery.11 With improvement of surgical techniques, better anaesthesia, blood transfusion services, and use of antibiotics, caesarean section is considered safe for both mother and baby over difficult vaginal delivery. With rising caesarean section rates, prenatal mortality/ maternal morality, cerebral palsy, and rate of vesicovaginal fistula have been reduced. Chronic pelvic floor problems like utero-vaginal prolapse, urinary stress incontinence and anal sphincter damage, and flatus and stools incontinence are less common in patients who had caesarean section deliveries.12 Caesarean section rate can be reduced by: 1. Having planned pregnancies 2. Proper booking in antenatal clinics 3. Advice about diet and regular exercise during pregnancy to avoid foetal macrosomia 4. External cephalic version (ECV) for uncomplicated breech presentation at 36-37 weeks as success rate of ECV is 50%. Such patients should be referred to consultants for ECV in time. 5. Strict control of diabetes with insulin, diet and exercise 6. Proper treatment and control of hypertension and preeclampsia to avoid iatrogenic premature delivery by caesarean section. 7. Encouragement of spontaneous labour, avoiding induction of labour with prostaglandins and oxytocics. Injudicious use of oxytocics causes foetal distress which usually needs delivery by caesarean section. 8. Avoiding post-maturity as delivery beyond 41 weeks of gestation would increase the incidence of caesarean section and instrumental delivery. J Ayub Med Coll Abbottabad 2012;24(3-4) 2 http://www.ayubmed.edu.pk/JAMC/24-3/Editorial.pdf Incidence of scar rupture for lower segment caesarean section is 1-1.5% and for classical caesarean section it is 5%. It means among 100 patients, one patient can have ruptured uterus. To save that one precious maternal life we have to manage those 100 patients with extreme care.